The reflection of "Bull" cult at the Bronze Age material culture of Azerbaijan - Avsharova, Irada (International Journal of Psychosocial Rehabilitation, 2020)
The study of archaeological monuments of worship remains as relevant as ever. People’s faith and faith in the nature of things, especially plants and animals, were carefully tuned. Some of them are successful, are considered useful, but some cause damage and become a symbol of evil. Archaeological artifacts are the same as the religious and ideological views of the first farmers who inhabit nomadic tribes. These are mostly animals, human figures and contains images. The period of the Neolithic and Bronze Age among the ancient tribes who lived in the minds of mythological animals, trust, respect and love occupies a special place. For this reason, they are images of animals on different objects, preparing figures. Since ancient times, people have chosen characters to distinguish between themselves and their people. The mythological ancient tribes that lived in the minds of research attribute a multitude of animals, mainly due to the powers of power. In addition to being a symbol of primitive mythology of power, depressive images took place.